Sprachatlas des Dolomitenladinischen und angrenzender Gebiete Volumen supplementarium - Goebl, Hans (Editions de Linguistique et de Philologie, 2012)
The volumes 7 contains supplementary information to the 1066 dialect maps of the volumes 1-5.